PSV-41 Antibacterial activity of ferulic acid and sodium chlorate against Escherichia coli F18 and K88 during incubations with porcine fecal bacteria. (5th December 2019) - Arzola, Claudio; Latham, Elizabeth; Anderson, Robin; Salinas-Chavira, Jaime; Castillo, Yamicela; Ontiveros, Marina; Felix-Portillo, Monserrath; Olivas-Palacios, Ana Luisa; Armendariz-Rivas, Ruth Lisbeth; Arzola-Rubio, Alejandro
Abstract: The influence of ferulic acid (FA) and sodium chlorate (SC) was evaluated in two trials on the growth of Escherichia coli F18 and K88 (F18 and K88) incubated with porcine fecal bacteria. Treatments were 2 levels of FA (0 and 5 mg/mL) and 2 levels of SC (0 and 10 mM/mL). In trial one, ½-strength Mueller Hinton broth mixed with porcine feces (0.5% w/v) was inoculated with a novobiocin and naladixic acid resistant F18-strain. This fecal suspension was transferred to tubes (3/treatment) and anaerobically incubated at 39 oC for enumeration at 0, 6 and 24 h using MacConkey agar supplemented with novobiocin and naladixic acid with aerobic incubation at 37 oC. An interaction (FA x SC) at 6 and 24 h was observed (P < 0.01). At 6 h of incubation, SC alone or combined with FA had the lowest counts (P < 0.05); FA alone was lower than control but higher than SC or SC+FA (P < 0.05). At 24 h, FA alone or combined with SC had the lowest counts (P < 0.05); SC was lower than control but higher than FA or SC+FA (P < 0.05). In trial 2 were used the same procedures of trial 1, except that K88 was used. There was an interaction at 6 h (P < 0.01) where the lowest counts were in FA+SC (P < 0.05). SC alone or FA alone were lower than control but higher than SC+FA (P < 0.05). There was no interaction at 24 h (P = 0.16), where FA reduced the K88 counts (P < 0.01), however it was not affected by SC (P = 0.12). In conclusion, SC reduced E. coli counts; however, at 24 h of incubation greater reductions were observed when FA alone or combined with SC was added into the incubation fluid with porcine feces.